The masonic criminal case against Luis Zuloaga, for being disloyal to the Rite of York - Vázquez Semadeni, María Eugenia (2022)
This paper analyzes the deep relationship in Mexico between Freemasonry and politics after its independence. Through the analysis of a Masonic trial against a member of the "Apotheosis de Hidalgo" lodge, in Chihuahua, we observe how Yorkino Freemasonry in Mexico became a center of political action, since it incorporated political elements into Masonic principles and practices. It influenced political practices of the republican order, such as elections. The text also shows the importance of the press and public debate, as well as the interaction between local and national politics, an interaction in which the local symbolic lodges largely contributed.